2014
DOI: 10.1016/j.jpsychires.2013.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity alterations in brain networks relevant to self-awareness in chronic cannabis users

Abstract: Chronic cannabis use was associated with significant effects on the tuning and coupling of brain networks relevant to self-awareness, which in turn are integrated into brain systems supporting the storage of personal experience and motivated behavior. The results suggest potential mechanisms for recreational drugs to interfere with higher-order network interactions generating conscious experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(93 citation statements)
references
References 61 publications
10
80
0
1
Order By: Relevance
“…In addition, PCC-right anterior insula connectivity strength correlated with duration of cannabis use. This finding is consistent with the Pujol and colleagues study (2014) showing that average joints per year positively correlated with PCC-right anterior insula connectivity strength. The anterior insula is a key component of the SN involved in interoceptive and visceral awareness (Caseras et al, 2013; Critchley et al, 2004) and functions along with the ACC and amygdala in integrating external and internal stimuli (Sutherland et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, PCC-right anterior insula connectivity strength correlated with duration of cannabis use. This finding is consistent with the Pujol and colleagues study (2014) showing that average joints per year positively correlated with PCC-right anterior insula connectivity strength. The anterior insula is a key component of the SN involved in interoceptive and visceral awareness (Caseras et al, 2013; Critchley et al, 2004) and functions along with the ACC and amygdala in integrating external and internal stimuli (Sutherland et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Together, these findings indicate that cannabis and tobacco use have differential effects on the DMN. It is important to note, however, that Pujol and colleagues (2014) did not report or control for cigarette use among their heavy cannabis users, and Weiland and colleagues (2014) did not report or control for cannabis use among their smoking sample. Consequently, findings from these studies may be confounded by co-occurring use.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our results are also in line with studies demonstrating altered brain network connectivity under the influence of drugs that induce psychotic symptoms (Diaconescu et al, 2010;Esposito et al, 2013;Pujol et al, 2013) and studies demonstrating altered connectivity in different stages of schizophrenia (Pettersson-Yeo et al, 2011). This may suggest that altered functional connectivity under the influence of delta-9-THC might be a plausible mechanism through which regular cannabis consumption increases the risk of development of schizophrenia.…”
Section: Discussionsupporting
confidence: 91%
“…These results match the resting-state functional connectivity when the pACC is treated as a seed [62]. Similarly, clinical work has shown changes of neural coupling between the medial PFC and other brain regions when patients process self-related information [63,64]. For example, researchers reported that altered self-awareness in Alzheimer's disease patients is associated with changes in functional connectivity between the medial PFC and other cortical midline structures and dorsolateral prefrontal cortex [63].…”
Section: Self-reference Enhances the Coupling Between Brain Regionssupporting
confidence: 62%